Brain Refrain and Human Capital Formation in Spain - Jose Blanco-Álvarez; Christopher Parsons; Sam Tang; Yong Wang (Institute of Labor Economics (IZA), 2022)
We examine how low and high skilled internal emigration causally affect investments in human capital at origin. We provide theoretical and empirical evidence of a disincentive mechanism through which individuals refrain from education should low skilled emigration prove a viable alternative. Our identification strategy leverages administrative records of labor contracts of differing skills signed at migrants' provincial destinations. We document large Brain Gain and Brain Refrain effects. Our results paradoxically demonstrate an improvement in human capital given the trajectory of the Spanish labor market over our sample period. When juxtaposed against provinces' net human capital positions however, most provinces lose.
Keywords: F22; O15; 330; brain drain; brain gain; brain refrain; internal migration; low skilled migration; high skilled migration